ORGANIC MATTER ADDITION AND ZINC STATUS IN CALCAROUS SOIL OF IRAQ - & et al., Rasheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The current investigation was conducted at 2014-2015 to determine the influence of levels and periods of addition of organic matter on Zinc availability in Iraqi calcareous soil. Experiments were conducted as a field experiment in a randomized complete block design (RCBD) using four replicates. Wheat, Al-Rasheed variety was used as a test crop. The entire field was equally dived in two divisions. One of the two divisions was cultivated to wheat and the second was left uncropped. Effect of five levels of organic matter as a peat namely 0, 25, 50, 75, 100 ton ha-1 were determined. Soils were analyzed to determine its physical and chemical characteristics. Soil samples were collected after 3, 30, 60, 90, 120, and 180 days for determining essential parameters and indicators that reflect the effect of the level of compost addition on Zinc availability. DTPA- Zn after 3, 30, 90, 120, 150 and 180 days are the least at 20-30 cm depth and the greatest at 0-10 cm depth. DTPA- Zn increased with increase of the level of OM addition. DTPA-Zn 90 days after addition in uncropped soil at 25 ton OM ha-1 addition was 1.55, 1.02 and 0.36 mg kg-1 Zn at 0-10, 10-20, 20-30 cm depths and it was 1.40, 1.05 and 0.78 mg kg-1 Zn at the same soil depths, for cropped soil, respectively. DTPA extractable Zn as affected by time of addition, over the entire period of addition, was higher in cropped soil than that in uncropped soil at 50 ton OM ha-1 addition level. DTPA- Zn in both cropped and uncropped soil was found to increase linearly with the time after addition.